1996
DOI: 10.1007/bf01271261
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of possible psychoactive effects of intravenous forskolin in depressed and schizophrenic patients

Abstract: Forskolin is a unique activator of adenylate cyclase that bypasses membrane receptors and directly raised levels of the second messenger cyclic AMP. Depressed patients and schizophrenic patients with negative symptoms have been reported to have reduced cyclic AMP levels. In the first study of forskolin in psychiatry, we gave iv forskolin in a 75 minute infusion to four depressed and five schizophrenic patients. All four depressed patients showed a transient mood elevation or stimulation, as did two of the five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 13 publications
(11 reference statements)
2
11
0
Order By: Relevance
“…The lithium-induced blockade of forskolin effects may take place at specific adenylate cyclase molecules whereas lithium's variable depression of activity may be due to effects on other signaling systems as well. In an open pilot study in depressed patient forskolin had antidepressant effects on behavior (Bersudsky et al, 1996), but other drugs that elevate cAMP levels, such as rolipram, have been shown to suppress locomotor activity in rodents (Wachtel, 1982) and to have antidepressant properties in humans (Horowski and Sastre-Y-Hernandez, 1985) and rats (Overstreet et al, 1992).…”
Section: Discussionmentioning
confidence: 97%
“…The lithium-induced blockade of forskolin effects may take place at specific adenylate cyclase molecules whereas lithium's variable depression of activity may be due to effects on other signaling systems as well. In an open pilot study in depressed patient forskolin had antidepressant effects on behavior (Bersudsky et al, 1996), but other drugs that elevate cAMP levels, such as rolipram, have been shown to suppress locomotor activity in rodents (Wachtel, 1982) and to have antidepressant properties in humans (Horowski and Sastre-Y-Hernandez, 1985) and rats (Overstreet et al, 1992).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, rolipram, an inhibitor of phosphodiesterase type 4 and cAMP breakdown, has antidepressant properties in preclinical and clinical tests (Bobon et al, 1988;Scott et al, 1991;O'Donnell, 1993). Moreover, forskolin, a plant diterpene that directly activates adenylyl cyclase, is also reported to have antidepressant efficacy in clinical trials (Bersudsky et al, 1996).…”
mentioning
confidence: 99%
“…While available so far only for nonhuman use, possible anticancer eects of cyclic AMP modulation makes their development for human use likely. Bersudsky et al (1996) recently reported mood-elevating properties of forskolin infusion in depressed patients and anergic schizophrenic patients. Since forskolin is a direct activator of intracellular cyclic AMP, these results support the concept of Wachtel (1989) that intracellular cyclic AMP levels in some brain cells aect mood.…”
Section: Discussionmentioning
confidence: 98%